2021
DOI: 10.3399/bjgpo.2021.0125
|View full text |Cite
|
Sign up to set email alerts
|

Vital signs, clinical rules, and gut feeling: an observational study among patients with fever

Abstract: BackgroundGeneral practitioners (GPs) decide which patients with fever need referral to the emergency department (ED). Vital signs, clinical rules and gut feeling can influence this critical management decision.Aimto investigate which vital signs are measured by GPs, and whether referral is associated with vital signs, clinical rules, or gut feeling.Design & settingprospective observational study at two out-of-hours GP cooperativesMethodduring two nine-day periods, GPs performed their regular work-up in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Repeated observational and qualitative studies have shown that the GFQ can be effectively used to assess the role of ‘gut feelings’ in GPs’ decision-making process in uncertain situations [ 10 , 11 , 15 ]. It has been shown that the sense of alarm correlated with a life-threatening situation for patients presenting with dyspnoea and/or chest pain [ 10 ], in line with other studies showing that GPs’ ‘gut feelings’ might predict clinical severe problems [ 16–18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Repeated observational and qualitative studies have shown that the GFQ can be effectively used to assess the role of ‘gut feelings’ in GPs’ decision-making process in uncertain situations [ 10 , 11 , 15 ]. It has been shown that the sense of alarm correlated with a life-threatening situation for patients presenting with dyspnoea and/or chest pain [ 10 ], in line with other studies showing that GPs’ ‘gut feelings’ might predict clinical severe problems [ 16–18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical intuition is a non-analytic, subconscious and instinctive process, through which physicians assess the severity of the patient's illness [8][9][10][11]. The ED physician's clinical intuition has demonstrated commendable discriminatory performance in previous studies, predicting adverse outcomes in ED patients (i.e.…”
Section: Introductionmentioning
confidence: 99%